2014
DOI: 10.5812/jjm.8556
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Identification of AmpC β-Lactamases Production in Gram-Negative Bacilli Isolates

Abstract: Background:AmpC type β-lactamases are commonly isolated from extended-spectrum Cephalosporin-resistant Gram-negative bacteria. Also, resistance appeared in bacterial species not naturally producing AmpC enzymes. Therefore, a standard test for the detection of the plasmid-mediated AmpC enzyme and new breakpoints for extended spectrum Cephalosporins are urgently necessary.Objectives:To detect plasmid and chromosomal mediated AmpC-β-lactamases in Gram negative bacteria in community and hospital acquired infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
5
28
2
Order By: Relevance
“…In the present study 14 of 49 (28.5%) cefoxitin resistant isolates were confirmed to possess PAmpC gene by multiplex PCR. Our result showed agreement with Egyptian studies previously conducted at Cairo University Hospital [12,23], where PAmpC prevalence were 26% and 28.3% respectively. This result came in agreement with another study Japoni-Nejad et al [19] that reported 19% prevalence of PAmpC genes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study 14 of 49 (28.5%) cefoxitin resistant isolates were confirmed to possess PAmpC gene by multiplex PCR. Our result showed agreement with Egyptian studies previously conducted at Cairo University Hospital [12,23], where PAmpC prevalence were 26% and 28.3% respectively. This result came in agreement with another study Japoni-Nejad et al [19] that reported 19% prevalence of PAmpC genes.…”
Section: Discussionsupporting
confidence: 93%
“…In our study cefoxitin susceptibility was used as screen test for AmpC. This was agreed by Gupta et al and Wassef et al [11,12].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The knowledge of potential risk factors for that resistance may help to limit its impact by enabling the implementation of effective control measures and judicious antimicrobial therapy (3). AmpC β-lactamases are either plasmid-or chromosomal-mediated (4). With regard to plasmid-mediated AmpC (pAmpC), no single phenotypic method is satisfactory for its detection; the combined application of phenotypic tests is necessary for the screening and confirmation of the presence of pAmpC-mediated resistance (5).…”
Section: Introductionmentioning
confidence: 99%
“…(Nasir et al, 2015) In a study at Egypt by Wassef M and Behiry I 86.4% (19/22) were chromosomally-mediated and 13.6 %( 3/22) plasmid-mediated AmpC. (Wassef et al, 2014) Amongst the 320 urinary Enterobacteriaceae isolates the inducible AmpC production was maximally detected by the ceftazidime-imipenem disk antagonism test (3.1%) and the noninducible isolates by AmpC disk test (2.2%). (Shevade and Agarwal, 2013) Cefoxitin and imipenem are strong inducers of the AmpC β-lactamases, whereas cefotaxime and ceftazidime are weak inducers.…”
Section: Figure2 Ampc Disk Testmentioning
confidence: 99%